2011
DOI: 10.1111/j.1600-0706.2011.18887.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtle differences in two non‐native congeneric beach grasses significantly affect their colonization, spread, and impact

Abstract: Comparisons of congeneric species have provided unique insights into invasion ecology. Most often, non‐native species are compared to native ones to look for traits predicting invasion success. In this study, we examine a different facet of congeneric comparisons in which both species are non‐native. Ecological variability among non‐native congeners might 1) lead to the inhibition or facilitation of either species’ ability to colonize and spread, 2) result in larger cumulative impacts due to synergies between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
255
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(265 citation statements)
references
References 35 publications
10
255
0
Order By: Relevance
“…It is not obvious whether this is a cause or an effect of tiller density. Soil organic matter increases with time in primary successional systems due to the facilitative effects of early plant colonizers (e.g., Chapin et al 1994, Lichter 1998, so it is possible that soil organic matter responds directly to A. breviligu- Hacker et al (2012) found that sand supply rates (cm sand deposition per month) differed among sites and were better predictors of tiller densities than were local climate factors. Ammophila breviligulata is adapted to the dune environment and actually dependent on moving sand and burial to maintain vigorous populations (Maun and Lapierre 1984).…”
Section: Discussionmentioning
confidence: 99%
“…It is not obvious whether this is a cause or an effect of tiller density. Soil organic matter increases with time in primary successional systems due to the facilitative effects of early plant colonizers (e.g., Chapin et al 1994, Lichter 1998, so it is possible that soil organic matter responds directly to A. breviligu- Hacker et al (2012) found that sand supply rates (cm sand deposition per month) differed among sites and were better predictors of tiller densities than were local climate factors. Ammophila breviligulata is adapted to the dune environment and actually dependent on moving sand and burial to maintain vigorous populations (Maun and Lapierre 1984).…”
Section: Discussionmentioning
confidence: 99%
“…A. arenaria and E. juncea differ in their vegetation characteristics: A. arenaria grows in dense patches, whereas E. juncea has a sparser growth form. This difference in growth form probably also results in a different dune morphology: A. arenaria forms higher "hummocky" shaped dunes, whereas E. juncea builds broader and lower dunes (Bakker, 1976;Hacker et al, 2012). The monitoring area is bisected by a low (maximum height of 7 m NAP, i.e.…”
Section: Study Sitementioning
confidence: 99%
“…Whether the latter also applies to nebkha dunes, is unknown. Differences in vegetation density between plant species are known to modify sand deposition (Arens, 1996;Hesp, 1983;Keijsers et al, 2014;Zarnetske et al, 2012), storm erosion (Charbonneau et al, 2017;Seabloom et al, 2013), and dune morphology (Du et al, 2010;Hacker et al, 2012;Hesp, 1988). Sheltering by other nebkha dunes can decrease the sand supply but can also reduce erosion by waves (Arens, 1996;Lima et al, 2015;Luo et al, 2014;Montreuil et al, 2013).…”
mentioning
confidence: 99%
“…Interactions among these species ultimately affect the composition of the plant community, and thus the structure of landscape itself. In the US Pacific Northwest, the introductions and subsequent invasions of two Ammophila beach grasses caused landscape-scale transformations of coastal dune shape [161]. This is surprising, given the dominant influence of the physical environment on coastal geomorphology [162].…”
Section: Effects Of Biotic Interactions On Landscape Structurementioning
confidence: 88%